Women’s Leadership in Pesantren in the Modern Era: A Study on the Leadership of Ibu Nyai Hj. Mundjidah Wahab - Hilwa Zumairotul Muna; Hilyah Ashoumi; Hidayatur Rohmah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the leadership style of Ibu Nyai Hj. Mundjidah Wahab in developing Pondok Pesantren Al-Lathifiyyah 2 and Al-Wahabiyyah 1 in the modern era. This research uses a qualitative approach with a biographical study type and a multisite design. Data collection techniques include in-depth interviews, observation, and documentation, while data analysis is conducted through data reduction, data presentation, and drawing conclusions using a triangulation approach to ensure data validity. The results of the study show that the leadership style of Ibu Nyai Hj. Mundjidah Wahab has democratic and participatory characteristics, charismatic qualities, maternal leadership (motherhood leadership), collaborative orientation, and adaptability in balancing traditional pesantren values with the demands of modernity. Her leadership is manifested through deliberative mechanisms, the active involvement of administrators and educators in operational decision-making, and firmness in determining strategic policies of the pesantren. In addition, the practice of delegation of authority and empowerment of administrators allows the pesantren to continue operating effectively even when the caretaker is not always physically present. This leadership is influenced by supporting factors such as public leadership experience, support from the pesantren family, solid internal cooperation, a structured management system, and public trust, as well as inhibiting factors such as time limitations, variations in human resource capacity, and challenges in adapting to modernity. This study concludes that the leadership style of Ibu Nyai Hj. Mundjidah Wahab represents a manifestation of adaptive leadership that combines the principles of deliberation, participation, delegation, and service. This leadership model contributes to the realization of effective and sustainable pesantren governance while remaining strongly rooted in Islamic values and pesantren culture.